Pesantren: Antara Transformasi Sosial Dan Upaya Kebangkitan Intelektualisme Islam - Chaer, Moh Toriqul (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2017)
Pesantren as a representation of a typical Islamic education Indonesia has a significant contribution in the intellectual life of the nation. Stigmatization of the pesantren education as a classic conservative and old-fangled, seem to need to be re-examined.. Learn how social function of religious schools is still required with considering repeated the role and dynamics of the boarding school in the community. Dynamics of modernity imposes a fundamental function of the pesantren which eventually resulted in the emergence of the reduction of cultural identity on boarding. The problem is the consequences and implications logical, when pesantren connected with modernity. This article studies focused their efforts on Pesantren maintain themselves as Islamic religious institutions to strengthen the tradition and transformed in the modern era. In the capacity of the boarding school as educational institutions and social culture. It will play a fundamental role in the function of society Indonesia in the middle of modernity.